Acquired thrombotic thrombocytopaenic purpura of an atypical, oligosymptomatic course in an adolescent girl - case report - Grażyna Waśka; Weronika Fijałkowska; Marta Badeńska; Andrzej Badeński; Agnieszka Książek; Renata Tomaszewska; Elżbieta Trembecka-Dubel; Maria Szczepańska (Termedia Publishing House, 2023)
Acquired thrombotic thrombocytopaenic purpura (TTP) in children is a rare immune-mediated haematological disease (iTTP) in which active thrombus formation and multiorgan symptoms resulting from ischaemia of specific organs occurs. A 16-year-old girl was admitted to the hospital with symptoms of haemorrhagic diathesis. Physical examination showed numerous small petechiae all over her body. Laboratory tests revealed thrombocytopaenia, increased parameters of inflammation, lactate dehydrogenase activity, and total bilirubin. Decreased a disintegrin and metalloproteinase with thrombospondin motifs, member 13 (ADAMTS-13) activity, and the ADAMTS-13 inhibitor were detected. At first, the symptoms were not specific enough, therefore initially some difficulties establishing a proper diagnosis occurred. Finally, the patient was diagnosed with primary autoimmune thrombocytopaenia and then underwent an adequate therapy with fresh frozen plasma (plasmapheresis and multiple infusions) combined with corticosteroids, which induced a sustained remission of the disease. The authors aimed to raise the awareness of the iTTP, especially with limited characteristic features, as presented, and highlight the significance of differential diagnosis.